ASEAN Countries on Overcoming US – China Trade War - Zuliyan, Muhammad Arief; Alfian, Muhammad Faizal (UIN ALAUDDIN MAKASSAR, 2024)
The trade war between the United States and China mostly has a negative impact to foreign policy in Indo-Pacific Region, included ASEAN countries. The US-China Trade war absolutely hamper ASEAN economicallyThe ASEAN nations are dealing with China-US relations as two great power states are taking big important role economically in ASEAN. This work is aim to question how ASEAN takes action from this situation to overcome the impact of Trade war and by using Neoliberalism, the paper would like to show the strategy ‘flexibility in interdependence’ which explains how the ASEAN economic integration could mitigate the problems and reducing the tensions using liberal interdependence. We conclude the flexibility in interdependence is based on two trade instrument including Generalized System Preference (GSP) and Regional Comprehensive Economic Forum (RCEP).